ROLE OF NICE CLASSIFICATION IN TRADEMARK REGISTRATION SYSTEM OF INDIA: A DESCRIPTIVE ANALYSIS - Manjhi, Manoj Kumar; Srivastava, Sanjay Prakash (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Technological innovations have exerted a far-reaching and transformative influence across nearly all domains of human existence, including the realm of economic activity. These shifts are permeating the sphere of intellectual property, notably reshaping the contours and parameters of trademark law, encompassing both the criteria for trademark eligibility and the scope of legal safeguards afforded to such marks. The Nice Agreement was adopted for the classification of goods and services for protection and registration of trademarks as per the dynamic needs of the market. This agreement provides a broader and more concise list of classifications of goods and services, which play an important role in the trademark registration system. This paper intends to examine the impact of Nice Agreement and classification of goods and services in registration of trademarks. How has the concept of classification of goods and services evolved and developed in trademark law, and what are the criteria for classification and determination of goods and services? How does the Nice Classification of Goods and Services relate to the trademark registration system, and what are the challenges encountered in implementing this provision? These questions would be answer with deep analysis of the Nice Agreement and Trademark Laws provisions. In conclusion section we have witnessed that Nice Classification is playing a pivotal role in trademark registration and the class of proposed trademarks are determined interpreted according to the nature of goods and a standard set up by rules and procedures.